La novella dannunziana e la sua vocazione alla scena - Puppa, Paolo (Archivio d’Annunzio, 2015)
Surely Gabriele d’Annunzio used the theatre as a support for his career. Apart from this, his dramas focus on the essential dynamics of obsessive metaphors and myths which were personal of the author. The theatre enables such dynamics to be fully realized. The essay explores La nave as a perfect paradigm of this approach, and also examines La figlia di Iorio and Le Martyr de Saint Sébastien, seeking gestures and developments which reveal impulses towards an endless metamorphosis. This applies to his characters as well, who are transformed from insecure teenagers into heroes who wield power over women and the masses. The combined elements of brutal sex and the search for spiritual purity are already to be found in his early novels, and are a hallmark throughout his work. It follows that silent cinema and great melodrama could only make these elements more explicit ― and here one can find a true legacy from Ibsen. The furious reaction of Catholics to the performance of La nave at La Fenice in Venice in 1908 was due to its most transgressive message: the juxtaposition of the prayers to the Holy Virgin Mary and the hymn to the goddess Venus.